(untitled) (Hakim: Jurnal Ilmu Hukum dan Sosial, 2026)
Digitalization in Indonesia has fundamentally shifted social interactions from physical domains into cyberspace, creating a complex legal phenomenon where netizens act as informal law enforcers through viral social pressure ("No Viral, No Justice"). This study aims to analyze the sociological emergence of digital vigilantism from a sociological jurisprudence perspective. Utilizing a Systematic Literature Review (SLR) guided by the PRISMA protocol, this research transparently screened 125 initial records from the Sinta database, yielding a final sample of 10 representative peer-reviewed articles published within a strict chronological boundary of 2021–2025. The results indicate that digital vigilantism is a functional manifestation of "Cyber Living Law"—an unwritten normative system driven by virtual community consensus to address the perceived stagnancy of formal law enforcement. Culturally, online public shaming behaves as a contemporary, non-physical adaptation of traditional customary sanctions. However, this study underscores a rigid normative demarcation between sociological legitimacy and formal legality: activities such as doxing and public shaming remain dogmatically non-permissible acts that violate written positive law (KUHP and the ITE Law). This paper concludes that Cyber Living Law must not be co-opted to legitimize cyber-anarchy; instead, it should be accommodated through future criminal policy reforms that incorporate cyber restorative justice mechanisms to harmonize public substantive justice with state legal certainty while preserving judicial independence from the pressure of virtual crowds.